A Mixed-Method Approach to Grounded Theory Regarding the MICE Industry at Busan Exhibition & Convention Center - Seieun Kim; Angellie Williady; Jue Wang; Hak-Seon Kim (Tourism and Hospitality)
The MICE (Meetings, Incentives, Conventions, and Exhibitions) industry plays a crucial role in driving the rapid growth of the local economy, and Busan is emerging as a significant MICE destination in Asia. This study uses online customer reviews to acquire a more in-depth insight into BEXCO (Busan Exhibition & Convention Center)’s customer experiences and satisfaction levels. A meticulously curated dataset of 2339 Google Maps reviews was assembled using the Outscraper tool. KH Coder 3 software was employed for a comprehensive analysis, including word frequency and co-occurrence analysis. The co-occurrence analysis revealed three prominent clusters of keywords: ‘MICE’ (Meetings, Incentives, Conferences, and Exhibitions), ‘Facility’, and ‘Environment’. This study also conducted exploratory factor analysis (EFA) and identified six factors that play a significant role in shaping customer experiences at BEXCO. Using these six factors, this study performed regression analysis to determine their impact on customer satisfaction. The results show that Food and Beverage, Venue, Event Space, and Parking Facilities significantly affect customer satisfaction. This research aims to bridge existing knowledge gaps, offering valuable insights that can contribute to the strategic development and enhancement of BEXCO’s offerings, thereby influencing the overall impact on the MICE sector in Busan.